Chitosan/Gelatin/Silver Nanoparticles Composites Films for Biodegradable Food Packaging Applications - Ediyilyam, Sreelekha; George, Bini; Shankar, Sarojini Sharath; Dennis, Thomas Thuruthiyil; Wacławek, Stanisław; Černík, Miroslav; Padil, Vinod V T (Polymers, 2021)
The food packaging industry explores economically viable, environmentally benign, and non-toxic packaging materials. Biopolymers, including chitosan (CH) and gelatin (GE), are considered a leading replacement for plastic packaging materials, with preferred packaging functionality and biodegradability. CH, GE, and different proportions of silver nanoparticles (AgNPs) are used to prepare novel packaging materials using a simple solution casting method. The functional and morphological characterization of the prepared films was carried out by using Fourier transform infrared spectroscopy (FTIR), UV-Visible spectroscopy, and scanning electron microscopy (SEM). The mechanical strength, solubility, water vapor transmission rate, swelling behavior, moisture retention capability, and biodegradability of composite films were evaluated. The addition of AgNPs to the polymer blend matrix improves the physicochemical and biological functioning of the matrix. Due to the cross-linking motion of AgNPs, it is found that the swelling degree, moisture retention capability, and water vapor transmission rate slightly decrease. The tensile strength of pure CH-GE films was 24.4 ± 0.03, and it increased to 25.8 ± 0.05 MPa upon the addition of 0.0075% of AgNPs. The real-time application of the films was tested by evaluating the shelf-life existence of carrot pieces covered with the composite films. The composite film containing AgNPs becomes effective in lowering bacterial contamination while comparing the plastic polyethylene films. In principle, the synthesized composite films possessed all the ideal characteristics of packaging material and were considered biodegradable and biocompatible food packaging material and an alternate option for petroleum-based plastics.
Keywords: antimicrobial; bio-nanocomposites; gelatin; chitosan; food packaging; silver nanoparticles